Kidnapped - Robert Louis,Stevenson; Wyeth, N. C. (Newell Convers), 1882-1945. (Dallas, TX : Zane Publishing, Inc. ; Chicago, IL : New SVE, Inc., 1996)
Allows the user to develop imaginative/narrative writing skills by selecting words that appeal to the senses. Teaches how to show specific actions, enhance descriptions, climactic scenes, and suspense to make the imaginary appear real to the reader. Helps the user to gain insight to Robert Louis Stevenson's use of imaginative/narrative writing skills by reading his classic novel Kidnaped.
System requirements: IBM-compatible 486DX/25MHz PC or Macintosh; Windows 3.1, 95 or System software.
Keywords: Fiction -- Technique; Narration (Rhetoric); Creative writing